Hunting for dwarf galaxies at cosmic dawn - Gelli, Viola; Salvadori, Stefania (Il Colle di Galileo, 2021)
The greatest space telescope ever built, the James Webb Space Telescope (JWST), will be launched in October 2021, allowing us to observe the distant Universe in depth. Thanks to sophisticated high-resolution cosmological simulations, we demonstrate that for the very first time JWST will observe hundreds of small sources which though very faint are fundamental in cosmic history: dwarf satellite galaxies.